NILAI-NILAI MORAL DALAM NOVEL SI ANAK KUAT KARYA TERE LIYE SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN SASTRA DI SEKOLAH DASAR - Aminah, Siti; Fatonah, Khusnul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Events related to declining morale often occur in society. Sadly, the perpetrators of the incident were minors. This research aims to find out the moral values contained in the novel Si Anak Kuat by Tere Liye. This research uses a qualitative approach with a content analysis method. The data in this study are moral values in the novel Si Anak Kuat by Tere Liye. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis is carried out using analysis tables. The results of the study show that the novel Si Anak Kuat by Tere Liye has four main moral values in accordance with James Rachels' theory. The most dominant moral values are courage (22 citations), moral values of generosity (11 citations), honesty (12 citations), and loyalty (9 citations). The novel can be used as an alternative medium for learning literature in elementary schools. Teachers can teach the moral values contained in novels through characters in the story. This aims to enable students to understand and apply life values and develop children's language skills.